Prácticas de radiofarmacia - Canellas, C. O.; Arguelles, María G.; Noto, María Gracia; Mitta, Aldo Emilio Antonio (Comisión Nacional de Energía Atómica; Argentina, 1982)
Fil: Canellas, C. O. Comisión Nacional de Energía Atómica; Argentina